¿Cómo innovan las fintech peruanas? Una aproximación a partir de un estudio de casos múltiple - Palomino Barchi, Gianella Judith (2019)
Fintech is a type of startup with a disruptive business model that provides digital financial services. One of its main competitive advantages is that they continually innovate, which is why the management of the resulting innovation relevant to them. In Peru, although the fintech ecosystem is growing, there are no empirical studies dealing with innovation in fintech. This article contributes to the knowledge of fintech and analyzes the management of its innovation processes by identifying key enablers and practices of the process. For this, a multiple case study of six fintech winners of the Startup Peru contest was carried out. The findings we have, due to the iterative and agile nature of fintech startups, some do not have a process of systematized innovation; however, there are key enablers and practices for managing the innovation process that allowthem to successfully launch new services to the market.